Nanoscale Defect Engineering and the Resulting Effects on Domain Wall Dynamics in Ferroelectric Thin Films. (10th March 2017) - McGilly, Leo J.; Sandu, Cosmin S.; Feigl, Ludwig; Damjanovic, Dragan; Setter, Nava
Abstract : Defect engineering is one of the cornerstones of the modern electronics industry. Almost all electronic devices include materials that have been doped by ion bombardment. For materials where crystallinity is essential, such as ferroelectrics, defect type and concentration can vastly influence properties and are often used to optimize device performance. This study shows a method to effectively control the density and position on the nanoscale of defect sites in thin films of Pb(Zr, Ti)O3 via focused ion beam microscopy. This allows for exceptional clarity of observation of the role of defects in nucleation, polarization switching, and domain wall interaction through investigation with piezoresponse force microscopy and transmission electron microscopy, adding insight to accepted but seldom‐demonstrated facts on defect‐induced effects. This nanoscale defect engineering can be used as a tool to control material properties, and furthermore, a route is demonstrated toward a practical application. Abstract : Low‐dose Ga + ion beams are used to effectively control the density and position on the nanoscale of defect sites in thin films of Pb(Zr, Ti)O3 via focused ion beam microscopy. This allows for clear observation of the role of defects in nucleation, polarization switching, and domain wall interaction through investigation with piezoresponse force microscopy and transmission electron microscopy.